`a)a+b+c=0`
`=>x_1=1,x_2=-7/3`
`b)9x^2+12x+4=0`
`Delta'=0`
`=>x_1=x_2=-b'/a=-2/3`
`c)3x^2+2sqrt2x=0`
`<=>x(3x+2sqrt2)=0`
`+)x=0`
`+)3x+2sqrt2=0`
`<=>x=-2sqrt2/3`
a) \(3x^2+4x-7=0\)
⇔ \(3x^2+7x-3x-7=0\)
⇔ \(x\left(3x+7\right)-\left(3x+7\right)=0\)
⇔ \(\left(x-1\right)\left(3x+7\right)=0\)
⇔ \(\left\{{}\begin{matrix}x=1\\x=-\dfrac{7}{3}\end{matrix}\right.\)
Vậy ....
b) \(9x^2+12x+4=0\)
⇔ \(\left(3x+2\right)^2=0\)
⇔ \(x=-\dfrac{2}{3}\)
Vậy ...
c) \(3x^2+2\sqrt{2}x=0\)
⇔ \(x\left(3x+2\sqrt{2}\right)=0\)
⇔ \(\left\{{}\begin{matrix}x=0\\x=\dfrac{-2\sqrt{2}}{3}\end{matrix}\right.\)
Vậy ...